"Reconstructions of the past distribution of Testudo graeca mitochondrial lineages in the Middle East and Transcaucasia support multiple refugia since the Last Glacial Maximum": A response to Turkozan et al. (2021). Issue 4 (October 2021) - , Flora Ihlow; , Uwe Fritz; , Peter Mikulíček; Rödder, Dennis
No abstract available